Carte des isles de Saint Pierre et Miquelon - Bellin, Jacques Nicolas, 1703-1772 (Paris (France), 1763)
Black and white. Prime meridian Paris. Compass rose with variation and rhumb lines. Decorative title cartouche. Relief shown by hachures and pictorially. Depth shown by soundings. Bar scales in common leagues and toises. Includes geographical note in decorative cartouche. Shows anchorages and undersea features. Inset map shows two rocks, in similar style. "Levée par ordre de M. Le Duc du Choiseul, Colonel Général des Suisses et Grisons Ministre de la Guerre et de la Marine, 1763 [.] Levé sure les lieux a 6 lignes pour cent toises par le Sr Fortin, ingenieur géographe." (title cartouche).